Participation Behavior in B2B Communities: - Akiko Nagahashi (Maketingu Janaru)
Since the 2000s, interest in brand communities has grown with the rise of the internet and social media. While many businesspeople participate in communities to solve work-related issues and improve their individual abilities, there has also been an increase in the number of communities that aim to share knowledge among customers, not only in the business-to-consumer (B2C) context, but also in the business-to-business (B2B) context. Two streams of community research targeting B2B began in 2000. The first is research that focuses on B2B brands within the framework of the brand community. The second is research on professional communities that targets knowledge sharing among professionals. This study is a literature review of B2B brand communities and professional communities that summarizes the theoretical background, antecedents, and consequences of participation behavior, while also presenting an important future research agenda.